Association of bone mineral density to dietary intake and predictors of breast cancer in premenopausal and postmenopausal Malaysian women - Norhayati Mohd Zain,; Kanaga Kumari Chelliah,; Vengkatha Priya Seriramulu,; Shantini Arasaratnam,; Poh, Bee Koon (Penerbit Universiti Kebangsaan Malaysia, 2017)
Daily food intake of women may affect their bone health by altering their bone mineral density (BMD) as the lack of certain nutrients may affect bone integrity whilst, BMD also can be a predictor of breast cancer. To date, many studies have been conducted to discuss on association of BMD and mammographic breast density (MBD) and how both are related to breast cancer risks but no consideration has been made on dietary intake. Therefore, this study was designed to determine the association of dietary intake with BMD and other breast cancer risk factors. A cross-sectional study on 76 pre- and postmenopausal women above 40 years underwent mammogram screening and Dual Energy X-ray Absorptiometry (DEXA) was conducted in Hospital Kuala Lumpur (HKL) for the duration of 1 year. Purposive sampling method was used to choose the respondents. Women who are diagnosed with breast cancer and underwent cancer treatment were excluded from this study. DEXA unit (Hologic Discovery W, Hologic, Inc) were used to measure BMD at the femoral neck and lumbar spine in grams per centimetre squared (g/cm2) and they were classified into normal and abnormal group based on the T-scores. The subjects were asked about their daily dietary pattern for a duration of three days using Diet History Questionnaire (DHQ). The mean of selected characteristics were compared between groups. Additionally, binary logistic regression was used to determine the association between diet intake with BMD and other risk factors of breast cancer. The total number of pre- and postmenopausal women who consented to participate in this study are equal. The mean age was 47.1 years and 54.9 years for premenopausal and postmenopausal women respectively. The results indicate only menopausal age of the women was statistically significant (p < 0.05). A number of 17% premenopausal and 9% of postmenopausal women showed to have family history of breast cancer, however, it was not statistically significant (p = 0.12). There was no significant difference in daily energy intake of food in both groups (p = 0.22). None of the nutrients in daily food intake showed to be statistically significant. Menstrual status showed an association with BMD with p < 0.05 and the remaining risk factors did not show any association. Logistic regression revealed that only menstrual status had correlation with BMD in both groups. This study provided the dietary pattern and the effects on bone health. The association of other risk factors of breast cancer with BMD were also analysed and most of it showed a negative association.